Classification of Cranberry Juice Consumers and Non-consumers with Urine Metabolome in a Double Blinded, Placebo-controlled, Cross-over Design Study (P06-032-19). (13th June 2019) - Zhao, Shaomin; Liu, Haiyan; Khoo, Christina; Gu, Liwei
Abstract: Objectives: To investigate urine metabolome changes after 3 days and 21 days cranberry juice consumption in a double blinded, placebo-controlled, cross-over intervention study and use statistical models to classify cranberry juice consumers and non-consumers by discriminant metabolites obtained in a previous 3-day open-labelled study. Methods: A double blinded, placebo-controlled, cross-over intervention study were conducted in 17 healthy young women aging 18–29 with normal BMI. Urine samples were collected at baseline, after 3 days, and after 21 days consumption of double strength cranberry juice or a placebo juice. Global metabolomic analysis of urine samples were conducted using UHPLC-Q-Orbitrap-HRMS. Results: Separation of two treatment groups were observed after both 3 days and 21 days juice consumption on OPLS-DA (orthogonal partial least squares discriminant analysis) models. In positive ionization, 14 discriminant metabolites were matched and used to do group classification of cranberry juice and placebo juice consumers. In negative ionization, 17 discriminant metabolites were matched and used to do group classification. Under double blinded condition, samples received the same treatment were regarded as one class. The correct classification rates were over 85% for all groups. Conclusions: Alteration of urine metabolome was observed among participants after 3 days and 21 days consumption. Discriminant metabolites found in a previous open-labeled study were able to build multivariate models and make classification with high correct classification rates. Funding Sources: This research is funded in part by Ocean Spray Cranberries, inc.